Chyawanprash: A Traditional Indian Bioactive Health Supplement - Sharma, Rohit; Martins, Natália; Kuca, Kamil; Chaudhary, Ashun; Kabra, Atul; Rao, Meda M; Prajapati, Pradeep Kumar (Biomolecules, 2019)
Chyawanprash (CP) is an Ayurvedic health supplement which is made up of a super-concentrated blend of nutrient-rich herbs and minerals. It is meant to restore drained reserves of life force (ojas) and to preserve strength, stamina, and vitality, while stalling the course of aging. Chyawanprash is formulated by processing around 50 medicinal herbs and their extracts, including the prime ingredient, Amla (Indian gooseberry), which is the world's richest source of vitamin C. Chyawanprash preparation involves preparing a decoction of herbs, followed by dried extract preparation, subsequent mixture with honey, and addition of aromatic herb powders (namely clove, cardamom, and cinnamon) as standard. The finished product has a fruit jam-like consistency, and a sweet, sour, and spicy flavor. Scientific exploration of CP is warranted to understand its therapeutic efficacy. Scattered information exploring the therapeutic potential of CP is available, and there is a need to assemble it. Thus, an effort was made to compile the scattered information from ancient Ayurvedic texts and treatises, along with ethnobotanical, ethnopharmacological, and scientifically validated literature, that highlight the role of CP in therapeutics. Citations relevant to the topic were screened.
Keywords: Humans; medicinal plants; Plant Preparations; marketing; nutraceutical; lidé; Functional Food; fytonutrienty; ayurveda; Marketing; health supplement; potravní doplňky; Dietary Supplements; rostlinné přípravky; Chyawanprash; Indian gooseberry; traditional medicine; funkční potraviny; Phytochemicals